Human brain anatomy in computerized images - Damasio, Hanna (Oxford University Press, 2005)
This book provides an atlas of the normal human brain based on three dimensional reconstructions of magnetic resonance scans obtained in normal living adults as well as neurological patients with focal brain lesions. It provides detailed descriptions of sulci and gyri and illustrates how they appear in different brains. The book shows how different slice orientations obtained in the same brain produce different images that can be anatomically misinterpreted, in normal brains as well as brains with lesions. The book also addresses quantitative differences between the human brain and the brains of apes; gray and white matter differences between the hemispheres; and differences related to gender, age, and congenital deafness.